Assessment of soil heavy metals for eco-environment and human health in a rapidly urbanization area of the upper Yangtze Basin - Zhongmin Jia (Nature Portfolio, 2018)
Abstract Soil pollution with heavy metals (HMs) has been attracting more and more interests, however, assessment of eco-environmental and human risks particularly in a rapidly urbanization area (the upper Yangtze) remains limited. Multiple modern indices were firstly performed for complete risk assessment of eco-environment and human health based on a high-spatial-resolution sampling. Averages of HMs were far below grade II threshold level of the Chinese Environmental Quality standards for soils, whereas Cd, As and Hg considerably exceeded the local background values. EF suggested overall moderate enrichments of Cd and Se, resulting in soils uncontaminated to moderately contaminated with them. Potential ecological risk index showed significant differences among Counties that were characterized by moderate risk. However, several sites were moderately to heavily contaminated with As, Cd and Hg by Igeo, resulting in that these sites were categorized as “considerable risk”, or “high risk”. Moreover, children were more susceptible to the potential health risk irrespective of the carcinogenic or non – carcinogenic risk. There were no significant carcinogenic and non – carcinogenic risks for adults, children however showed significant non – carcinogenic effect. Our first assessment provided important information for policy making to reduce the potential effects of soil contamination on human and eco-environment.